Moluscos asociados a las raíces sumergidas del mangle rojo Rhizophora mangle, en el Golfo de Santa Fe, Estado Sucre, Venezuela - Márquez, B; Jiménez, M (Revista de Biología Tropical, 2002)
A qualitative and quantitative monthly study of the mollusks community associated to the submerged roots of the red mangrove, Rhizophora mangle (L.), between October of 1998 and September of 1999, in six stations of the Gulf of Santa Fe, (Sucre State, Venezuela). Were collected 4 704 specimens, 45 species of mollusks were identified (22 gastropods, 15 bivalves and 8 chitons). The most abundant species were: Crassostrea rhi - zophorae, Isognomon bicolor, I. alatus and Brachidontes exustus. The highest values in diversity and evenness, and the smallest dominant values, were in the stations three and four, while the opposed happened in the stations one and two. The analysis of likeness showed that in the first five stations the space variations in the composition of the community are bigger than the temporary variations, while in the station six the temporary differences prevail. They were factors that could be important to determine the structure of the community, as vicinity to other ecosystems and/or specific biological aspects of the species like adaptations to fluctuating conditions, nutritious habits and migration in search of shady and protected atmospheres.